Delay in the Diagnosis of Parkinson S Disease in a Chilean Public Hospital - Lay-Son-Rivas, L (SOC MEDICA SANTIAGO, 2015)
Background: Early diagnosis is fundamental in patients with Parkinson s disease (PD) to improve their quality of life. Aim: To determine the latency in the diagnosis of Parkinson s disease (PD) after the onset of motor symptoms. Patients and Methods: Prospective study carried out during 16 months in a public hospital. Two hundred newly diagnosed patients aged 41 to 90 years (50% women), were included and analyzed. Results: The lapse between the first symptom -more commonly tremor- and the diagnosis made by a neurologist ranged from I to 84 months (19.1 +/- 13.8). In 39% of patients, it was done in the first year, in 26% during the second year and in 35% of patients, it took more than two years. The referral by a general practitioner had a delay ranging from 1 to 36 months. Sixty nine and 95% of patients were evaluated within the first 6 months after referral if they came from primary care or the same hospital, respectively. Twenty six percent of patients were classified in stages III to V of Hoehn & Yahr s staging and the Parkinson s Disease Rating Scale motor examination ranged from 5 to 81 points, mean 24 (+/- 12.8). Conclusions: The diagnosis of PD has a delay in a public hospital that could be influenced by the referral system.